Partial toxicity tests of copper (Cu2+), zinc (Zn2+) and cyanide (CN-) for young cobia fishes (Rachycentron canadum) with 45 day-old - Dung, Le Quang; Cu, Nguyen Duc (Academia Journal of Biology, 2014)
The partial toxicity tests of copper (Cu2+), zinc (Zn2+) and cyanide (CN-) for young cobia fishes with (Rachycentron canadum) 45 day-old were conducted in the Doson station during ten days (yr 2005). These three toxic substances affected strongly the growth of the cobia fish (size and weight), even at the lowest treated concentration. The LC50 values of copper, zinc and cyanide were 0.32 mg/l; upper 1mg/l and 0.049 mg/l, respectively. Based on the calculated results of NOEC and LOEC, we have determined the safe concentrations of these two heavy metals and cyanide for the environmental aquaculture of the cobia fish which were lower than 0.025 mg Cu/l, 0.5 mg Zn/l and 0.005 mg CN/l respectively. The results is also showed that cyanide was the most toxic to Cobia, followed by copper and zinc.